Highly efficient polyethylene glycol‐functionalised gold nanorods for photothermal ablation of hepatocellular carcinoma cells - Xingyu Du; Wei‐Chih Lin; Hsing‐Hao Su (IET Nanobiotechnology)
Gold nanorods (GNRs) with exceptional photothermal properties have held promising potential for application in the biomedical field. In this study, the authors achieved photothermal ablation by polyethylene glycol (PEG)‐functionalised GNRs. Well‐dispersed and uniform GNRs were produced through a seed‐mediated growth method. A thermal camera was used to scrutinise the temperature distribution and efficiency of the photothermal properties of the GNRs, which were irradiated by an 808 nm laser on a silicon chip. They observed that the GNRs provided about a 5°C temperature increase and produced hyperthermia efficiently. Since GNRs need to be surface tailored with a biocompatible material rather than cetyltrimethylammonium bromide (CTAB), they chose methoxyl PEG thiol to modify the GNRs. By taking advantage of the alkaline environment that assists this functionalisation, they accomplished about 89% removal of CTAB and identified a PEG layer on the surface of the GNRs. The GNR biocompatibility was considerably improved without any shift of the optical properties. Hepatocellular carcinoma cells were incubated with GNRs for 24 h and then were irradiated with a near‐infrared laser for 3 min. Few cells remained alive, which demonstrated the photothermal ablation ability of the GNRs.